Genome wide analysis of stress responsive WRKY transcription factors in Arabidopsis thaliana - Shaiq Sultan; Muhammad Amjid Ali; Rana Muhammad Atif; Farrukh Azeem; Habibullah Nadeem; M. Hussnain Siddique; Ertuğrul Filiz; Khadim Hussain; Amjad Abbas (Turkish Journal of Agriculture: Food Science and Technology)
WRKY transcription factors are a class of DNA-binding proteins that bind with a specific sequence C/TTGACT/C known as W-Box found in promoters of genes which are regulated by these WRKYs. From previous studies, 43 different stress responsive WRKY transcription factors in Arabidopsis thaliana, identified and then categorized in three groups viz., abiotic, biotic and both of these stresses. A comprehensive genome wide analysis including chromosomal localization, gene structure analysis, multiple sequence alignment, phylogenetic analysis and promoter analysis of these WRKY genes was carried out in this study to determine the functional homology in Arabidopsis. This analysis led to the classification of these WRKY family members into 3 major groups and subgroups and showed evolutionary relationship among these groups on the base of their functional WRKY domain, chromosomal localization and intron/exon structure. The proposed groups of these stress responsive WRKY genes and annotation based on their position on chromosomes can also be explored to determine their functional homology in other plant species in relation to different stresses. The result of the present study provides indispensable genomic information for the stress responsive WRKY transcription factors in Arabidopsis and will pave the way to explain the precise role of various AtWRKYs in plant growth and development under stressed conditions.